Plants and literature : essays in critical plant studies. - Laist, Randy. (Critical Plant Studies, 2013)
Myth, art, literature, film, and other discourses are replete with depictions of evil plants, salvific plants, and human-plant hybrids. In various ways, these representations intersect with "deep-rooted" insecurities about the place of human beings in the natural world, the relative viability of animalian motility and heterotrophy as evolutionary strategies, as well as the identity of organic life as such . Plants surprise us by combining the appearance of harmlessness and familiarity with an underlying strangeness. The otherness of vegetal life poses a challenge to our ethical, philosophical, and existential categories and tests the limits of human empathy and imagination. At the same time, the resilience of plants, their adaptability, and their integration with their habitat are a perennial source of inspiration and wisdom. Plants and Literature: Essays in Critical Plant Studies examines the manner in which literary texts and other cultural products express our multifaceted relationship with the vegetable kingdom. The range of perspectives brought to bear on the subject of plant life by the various authors and critics represented in this volume comprise a novel vision of ecological interdependence and stimulate a revitalized sensitivity to the relationships we share with our photosynthetic brethren.